2015
DOI: 10.1186/s13643-015-0084-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for hospital re-presentation among older adults following fragility fractures: protocol for a systematic review

Abstract: BackgroundAfter being discharged from hospital following the acute management of a fragility fracture, older adults may re-present to hospital emergency departments in the post-discharge period. Early re-presentation to hospital, which includes hospital readmissions, and emergency department presentations without admission may be considered undesirable for individuals, hospital institutions and society. The identification of modifiable risk factors for hospital re-representation following initial fracture mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The protocol for this systematic review and meta-analysis has previously been reported and is summarized below [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The protocol for this systematic review and meta-analysis has previously been reported and is summarized below [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…A third author (SMM) arbitrated any unresolved disagreements arising during any stage in the search and screening process. Further details about the search and selection strategy were outlined in the protocol [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Perception of risks associated with discharge is known to impact discharge decision-making and discharge destination (Atwal, McIntyre & Wiggett 2012). These risks include adverse events occurring after discharge, such as failed discharge (Mathew et al 2015), falls at home (Worley, Barras & Grimmer-Somers 2010) and, in extreme cases, death (Yu et al 2011). Clinicians perceive additional risks associated with discharge planning, with these risks being linked closely to accountability and blame in the event of negative outcomes (Bowling & Ebrahim 2001).…”
Section: Introductionmentioning
confidence: 99%